Design and implementation of robot control system for multistory buildings - Naqaa Luqman Mohammed; Mothanna Sh. Aziz; Omar Ibrahim AlSaif (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The advancement of technology, make robots have more attention from researchers to make life of mankind comfortable. This paper deals with the design of an itemized control system prepared for window cleaning/maintenance of towers and multistory buildings which can be aided to simulating human activities. These activities (washing, coating, wiping, climbing, and maintenance events) normally achieved by specialized personal. The designed control system was prepared to guide the units of the required job to move freely along the outside surface of a window with a fairly enough area and mediate time for achieving the desired goal. The system design is implemented using Arduino kit, due to facilities in program and control of cleaning windows through infer the stepper motor movement and rotation. The controller has been achieved as real time system (30 msec.), it is done throw control of three stepper motor by taken in consideration the speed of the motors (π/3000 rad/sec) and the time can be adjustable within the cleaning area that the device covering it.